Review of Literature: Genes Related to Postaxial Polydactyly - Verma, Prashant Kumar; El-Harouni, Ashraf A. (Frontiers in Pediatrics, 2015)
Background: Postaxial polydactyly (PAP) is one of the commonest congenital malformations and usually is associated to several syndromes . There is no primary investigational strategy for PAP cases with single gene disorder in literature. PAP cases with single gene disorder can be classified according to common pathways and molecular basis. Molecular classification may help in diagnostic approach. Materials and Methods: All single gene disorders associated with PAP reported on Pub Med and OMIM are analyzed and classified according to molecular basis. Results: Majority of genes related to cilia structure and functions are associated with PAP, so we classified them as ciliopathies and non-ciliopathies groups. Genes related to Shh-Gli3 pathway was the commonest group in non ciliopathies. Conclusions: Genes related to cilia are most commonly related to PAP due to their indirect relationship to Shh-Gli3 signaling pathway. Initially PAP may be the only clinical finding with ciliopathies so those cases need follow up. Proper diagnosis is helpful for management and genetic counseling. Molecular approach may help to define pleiotropy. Key word: Postaxial polydactyly (PAP), molecular approach, hedgehog protein, sonic (Shh), signal pathways, gene, cilia